2010
DOI: 10.1177/1359105310364169
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Religiosity, Social Support, and Stress-related Growth in Protecting Against HIV Risk among Transgender Women

Abstract: Transgender women completed questionnaires of religiosity, social support, stigma, stress-related growth, and sexual risk behavior. In a multivariate model, both social support and religious stressrelated growth were significant negative predictors of unprotected anal sex, but religious behaviors and beliefs emerged as a significant positive predictor. The interaction between religious behaviors and beliefs and social support was also significant, and post-hoc analyses indicated that high-risk sex was least li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 55 publications
(83 reference statements)
0
49
0
Order By: Relevance
“…Various aspects of religiosity have been conceptualized and operationalized in different ways, including as individual and collective beliefs, worship practices, and traditions used as coping strategies (Rew and Wong 2006). Religiosity has been found to be related to mental and sexual health outcomes Scott et al 2006;Sinha et al 2007;Turner-Musa and Lipscomb 2007) and is typically theorized to be protective (Cotton and Berry 2007;Cotton et al 2006), as religious beliefs and practices have been identified as important components of resilience to stress (Golub et al 2010). Employing religious beliefs and practices to cope with stressful life events has been shown to be associated with higher self-esteem, better life satisfaction, improved cognitive functioning, and less depressive symptoms (Pargament et al 2004;Park 2006;Yakushko 2005).…”
Section: Juvenile Justice Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Various aspects of religiosity have been conceptualized and operationalized in different ways, including as individual and collective beliefs, worship practices, and traditions used as coping strategies (Rew and Wong 2006). Religiosity has been found to be related to mental and sexual health outcomes Scott et al 2006;Sinha et al 2007;Turner-Musa and Lipscomb 2007) and is typically theorized to be protective (Cotton and Berry 2007;Cotton et al 2006), as religious beliefs and practices have been identified as important components of resilience to stress (Golub et al 2010). Employing religious beliefs and practices to cope with stressful life events has been shown to be associated with higher self-esteem, better life satisfaction, improved cognitive functioning, and less depressive symptoms (Pargament et al 2004;Park 2006;Yakushko 2005).…”
Section: Juvenile Justice Systemmentioning
confidence: 99%
“…However, religiosity may be a double-edged sword for some LGBT individuals (Golub, et al 2010), particularly black individuals demonstrating non-normative gender and sexuality. While religiosity and affiliation may help counter some oppression related to race, religious institutions likely do not offer parallel benefits related to gender nonconformity and marginalized sexualities (Graham 2012).…”
Section: Faith-based Institutionsmentioning
confidence: 99%
“…While the physical and psychological health and well-being of Black transgender women have long been studied, it appears that their resilience has only recently been examined (Eyre, Guzman, Donovan, & Boissiere, 2004;Golub, Walker, Longmire-Avital, Bimbi, & Parsons, 2010;Koken, Bimbi, & Parsons, 2009; National Gay and Lesbian Task Force [NGLTF], 2011). Although there is not an abundance of resilience-related literature about transgender individuals, it appears that for some Black transgender men and women, both their connection to members of their racial community and personal traits facilitate the development of resilience.…”
Section: Resilience In Black Transgender Individualsmentioning
confidence: 97%
“…Transgender youth have an elevated rate of emotional problems and disorders associated with trauma, including posttraumatic stress disorder, depression, anxiety, and suicide (Gomez-Gil et al, 2012;Liu & Mustanski, 2012;Roberts et al, 2012;Weinrich, Atkinson, McCutchan, & Grant, 1995). Furthermore, much of the psychological stress associated with transgender identities is thought to be attributable to familial and societal reactions to gender non-conformity rather than to the identity itself (Egan & Perry, 2001;Golub, Walker, Longmire-Avital, Bimbi, & Parsons, 2010;Yunger, Carver, & Perry, 2004). Therefore, encouraging tolerance through education about gender diversity could have profound effects on young people's emotional health (Stieglitz, 2010).…”
Section: Gender Identity Versus Gender Dysphoriamentioning
confidence: 95%